Polymorphonuclear leukocytes occlude capillaries following middle cerebral artery occlusion and reperfusion in baboons - del Zoppo, G J; Schmid-Schönbein, G W; Mori, E; Copeland, B R; Chang, C M (Stroke (1970), 1991)
Microvascular perfusion defects may accompany sustained occlusion and subsequent reperfusion of the middle cerebral artery; however, the nature of such "no-reflow" defects remains unclear. In the absence of antithrombotic pretreatment, we documented lenticulostriatal microvascular flow integrity following 3-hour middle cerebral artery occlusion and 1-hour reperfusion in a baboon occlusion/reperfusion model by two methods identifying 1) microvascular occlusion and 2) microvascular patency. Microvascular "no-reflow" involved capillaries (vessels of 4.0-7.5 microns diameter) of the lenticulostriatal territory. Capillary reflow included 27-39% of all capaillaries in two subjects, indicating a significant reduction of perfusion from normal (2p = 0.045). In identical experimental preparations, single polymorphonuclear leukocytes completely occluded 4.7% of microvessels of capillary diameter in randomly selected fields, partially occluded 3.5% of postcapillary venules, and occluded 40% (four of 10) of capillaries in linear reconstruction along a 110 microns length. Circumferential contact between polymorphonuclear leukocytes and the luminal endothelial cell membranes was documented, with an intrecellular gap of, at most, 160 nm. Fibrin was found with degranulated platelets when the latter were associated with granulocytes, but not with polymorphonuclear leukocytes alone. The finding of capillary-obstructing polymorphonuclear leukocytes in the microvascular bed following middle cerebral artery reperfusion in focal ischemia in this model satisfies an essential requirement for postulating their role in early microvascular injury and the "no-reflow" phenomenon.